Value and price of multi-indication cancer drugs in the USA, Germany, France, England, Canada, Australia, and Scotland - Michaeli, Daniel; Mills, Mackenzie; Kanavos, Panos (Applied health economics and health policy, 2022)
Oncology drugs are often approved for multiple indications, for which their clinical benefit varies. Aligning a single price to this differing value remains a challenge. This study examines the clinical and economic value, price, and reimbursement of multi-indication cancer drugs across seven countries, representing different approaches to value assessment, pricing, and coverage decisions: the USA, Germany, France, England, Canada, Australia, and Scotland.
Gesehen am 26.09.2023